Cost analysis of childhood asthma in Iran: A cost evaluation based on referral center data for asthma and allergies - Mohammad Ali Rezvanfar; Abbas Kebriaeezadeh; Mostafa Moein; Shekoufeh Nikfar; Zahra Gharibnaseri; Akbar Abdollahi-Asl (Wolters Kluwer Medknow Publications, 2013)
Objective: Asthma as the most common chronic disease in childhood reduces the quality of life of children and their families. We aimed to estimate the cost of managing childhood asthma in Iran and to examine its variability depending on asthma severity. Methods: The cost of asthma was estimated by building a cost assessment model regarding the factors that influence the cost of asthma in children including age and sex distribution, prevalence of disease severity, level of resource utilization depending on disease severity (3 groups of controlled, partly controlled and uncontrolled were defined). The model was comprised of both medical (cost of medication, physician visit and respiratory tests) and non-medical (transportation and hoteling) costs. Furthermore, the average family income in each category was figured and the share of asthma managing costs from the average income was calculated in different groups. Findings: According to model, the total cost of childhood asthma in Iran was around 516.5 million dollars. Moreover, direct medical cost represented 49% of the total costs, among which 66% accounting for medication cost. Direct non-medical costs were estimated 51% with the majority (93%) expended on transportation. In addition, the mean annual cost per child was approximately 466 dollars. In addition, the results indicate the vast majority of patients (46%) are categorized in the uncontrolled group. Conclusion: The cost of childhood asthma in Iran is extremely high comparing to the average income of Iranian families in all categories of asthma severity. Considering the high amount of transportation cost, the accessibility of asthma treatment does not appear to be acceptable. The major source of costs is found to be related to medicine expenditure. Since it has been proven that using medicine does not necessarily result in a well-controlled disease status, alternative approaches should be considered in asthma management.